Strike at the root: exploring the transferability of heat stress tolerance in tomatoes by reciprocal grafting - Biermann, Robin T.; Bach, Linh T.; Steuer, Christian M.; Reimer, Julia J.; Schwarz, Dietmar; Börnke, Frederik (Frontiers in Plant Science, 2025)
Heat stress (HS) poses a significant threat for tomato (Solanum lycopersicum L.) cultivation, leading to reduced yield throughout the production cycle. In addition to breeding, a promising approach to enhance HS tolerance is through grafting. For this, rootstocks obtained from tolerant genotypes are joint with susceptible scions that possess superior fruit traits. This study aims to test whether a priori knowledge of tolerance levels can be used to facilitate the identification of suitable grafting combinations, while simultaneously exploring molecular and physiological changes caused by grafting that further our understanding of the transferability of HS tolerance by grafting. The HS tolerance of tomato plants was evaluated using information about biomass development and flowering traits obtained for a diversity panel of 56 tomato genotypes comprising Mediterranean landraces cultivated under control (22/18°C) and HS (35/25°C) conditions. As result genotype T12 was identified with superior HS tolerance. In addition to this, a genotype with inferior HS tolerance, T48, was selected to perform reciprocal grafting experiments. Here transcriptomics data obtained from leaf tissue of grafted plants after a seven-day treatment period indicated global changes in gene expression with a special impact on components of the photosystem. Alongside, transcription factors and regulators such as ARID (Solyc01g111280.3.1), DDT (Solyc11g006200.2.1), GNAT (Solyc02g064690.3.1), and Jumonji (Solyc01g006680.4.1) were identified as potentially important targets for tolerance breeding. Long-term cultivation of grafted plants including eleven weeks of treatment supported the tolerance classification of the genotypes by the means of biomass and yield. Eventually, yield data indicated that the HS susceptible genotype (T48) lowered the yield of the usually tolerant scion (T12). Observed influences on the photosystem of the grafted plants were associated with the treatment rather than the grafting. In summary, these experiments indicated that HS tolerance or susceptibility, respectively can be conferred by grafting. However, more sophisticated screening techniques might be needed to successfully predict stress alleviation by grafting pair selection. Eventually, HS adaptation responses of the tomato plants might offer a potential for targeted breeding or engineering of tolerant genotypes, with a special focus on genes involved in epigenetic remodelling.